2020
DOI: 10.5204/ijcjsd.v9i1.1467
|View full text |Cite
|
Sign up to set email alerts
|

Who is Transitioning out of Prison? Characterising Female Offenders and Their Needs in Chile

Abstract: The last decades’ increase in female incarceration has translated into an increasing number of women being released from prison. Understanding their characteristics and criminal trajectories can enlighten us regarding the different needs of women upon re-entering society after incarceration. Drawing on data from the Reinserción, Desistimiento y Reincidencia en Mujeres Privadas de Libertad en Chile study, this article identifies different profiles among a cohort of 225 women who were released from prison in San… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 27 publications
(30 reference statements)
1
2
0
1
Order By: Relevance
“…Currently, there are 2957 sentenced and 1359 unsentenced women in correctional facilities across the country, which, in a total carceral population of 162,875, denotes that women make up less than 3% of the entire South African incarcerated population (DCS, 2019). From the statistics listed above, we can conclude that the population of incarcerated women in South Africa is a tiny minority compared to their male counterparts, which is consistent with overseas literature (Adams, 2020;Arnull & Stewart, 2021;Epstein, 2014;Larroulet et al, 2020) The United Nations (UN) reports that incarcerated women experience augmented risks of abuse throughout their adolescent and adult lives, coupled with high instances of mental health disorder diagnoses, including substance use disorders resulting from self-medicating due to histories of trauma (UN Special Rapporteur on Violence against Women, 2013). They also have an increased likelihood of being the sole providers and caretakers of children prior to incarceration, as well as a history of employment in low wage, entry-level positions (UN Handbook on Women and Imprisonment, 2014).…”
supporting
confidence: 81%
“…Currently, there are 2957 sentenced and 1359 unsentenced women in correctional facilities across the country, which, in a total carceral population of 162,875, denotes that women make up less than 3% of the entire South African incarcerated population (DCS, 2019). From the statistics listed above, we can conclude that the population of incarcerated women in South Africa is a tiny minority compared to their male counterparts, which is consistent with overseas literature (Adams, 2020;Arnull & Stewart, 2021;Epstein, 2014;Larroulet et al, 2020) The United Nations (UN) reports that incarcerated women experience augmented risks of abuse throughout their adolescent and adult lives, coupled with high instances of mental health disorder diagnoses, including substance use disorders resulting from self-medicating due to histories of trauma (UN Special Rapporteur on Violence against Women, 2013). They also have an increased likelihood of being the sole providers and caretakers of children prior to incarceration, as well as a history of employment in low wage, entry-level positions (UN Handbook on Women and Imprisonment, 2014).…”
supporting
confidence: 81%
“…Un aspecto particular que se está volviendo cada vez más problemático es el proceso de retorno a la comunidad por parte de las personas privadas de libertad, a medida que van dejando la cárcel. Esta etapa es clave en los procesos de reinserción social (Larroulet et al, 2019). En este sentido, existe limitada evidencia empírica sistemática sobre la magnitud, concentración y covariables asociadas al retorno a la comunidad de ex reclusos/as (Sanhueza, 2014).…”
Section: Salir De La Cárcel Y Retornar a La Comunidadunclassified
“…In sum, studies revealed that women characterized by a lifestyle of involvement in offenses have higher rates of recidivism and a more complex criminal pattern, with propensity for violence in the prison context (Larroulet et al, 2020). Additionally, negative social support mechanisms can propagate criminal prospects originating in society, as well as in prison, and prisoners with longer criminal careers and longer sentences tend to show higher rates of prison infractions (Jiang & Winfree, 2006).…”
Section: Criminal Lifestyle and Prison Adjustmentmentioning
confidence: 99%